The effect of a community mental health training program for multidisciplinary staff - Bing Xiang Yang (2018)
© 2017. Background: Primary health workers play a critical role in providing health education to people with mental disorders. In China community health workers working with people with mental health problems lack experience and training in this area. Additionally, coordination between hospital and community staff is not well established. The aim of this study was to provide an interdisciplinary community mental health training program and to evaluate the effect of the training on staff knowledge about mental health and confidence in their roles. Methods: A three-day community mental health training program was offered specifically for interdisciplinary mental health professionals. Using a one-group pre-test post-test design, participants completed a self-assessment of mental health concepts and program evaluation which included asking participants to rate their satisfaction using a five-point Likert scale and to respond to open-ended questions. Results: Forty-eight participants including health professionals from colleges, hospital and community health centers were recruited. Only 8.7% of participants had ever received community mental health training. Post-test evaluation demonstrated improvements in knowledge, and most participants were very satisfied with the program. Conclusion: The findings indicate that this brief interdisciplinary training program had a positive effect in improving knowledge about community mental health concepts and confidence in dealing with people with mental health disorders for multidisciplinary staff working in primary health care areas.